Edukasi Resiko Penularan Penyakit Melalui Sampah pada Pemulung Sampah di Tempat Penampungan Sementara Kelurahan Bukit Tunggal Kota Palangka Raya - Suratno Suratno; Nurhalina Nurhalina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Waste pickers are the riskiest group for diseases transmission through waste. Waste pickers have no sufficient knowledge about Personal Protective Equipment usage at work. Likewise, several waste pickers at Temporary Shelters located in Kelurahan Bukit Tunggal, Jekan Raya, Palangka Raya, Indonesia. This community service aimed to provide education and training about the reduction of disease transmission risks through waste at Temporary Shelters. These activities involved field surveys, interviews, education and outreach, training and demonstrations, and distribution of Personal Protective Equipment for waste pickers. The solution offered to solve the problems is to educate on disease transmission risks through waste, education, training and demonstration of PPE usage at work, and distribution of Personal Protective Equipment for waste pickers. The community service for 27 waste pickers in several TPS located in Bukit Tunggal was well implemented. The survey result shows the level of usage of Personal Protective Equipment on waste pickers, which is Not Wear 36.25%, Use Non-Routine 16.03% and Use Routine 47.5%. This series of activities can improve the scavenger's insights into the dangers and prevention of transmitting disease through waste.